KAJIAN SPASIAL VIHARA AVALOKITESVARA PAMEKASAN - Sahid, Ali Umar; Setyabudi, Irawan; Santoso, Dian Kartika (Aksen : Journal of Design and Creative Industry, 2024)
Pamekasan Avalokitesvara Vihara is a place of worship for Buddhists and also a tourist spot for all believers, both Buddhists and non-Buddhists. Located in Candi Village, Polagan District, Pamekasan City. This monastery is often used as a place of worship and tourism, studying the history of Buddhist culture, or even just for recreation. It started with the discovery of four statues in the Talang Siring beach area around three hundred years ago. Around the 1800s, the original monastery building was burned down, efforts to rebuild it were carried out in 1951. Currently, the monastery building is still being renovated in stages to get closer to the initial building form, apart from that there is also the addition of a new building function, namely a monk’s shrine. The problem faced by researchers is how to identify the use of space and the spatial dynamics of the spaces at the Pamekasan Avalokitesvara Vihara, in addition to the lack of vegetation arrangement and facility maintenance. This is due to the need to carry out architectural identification and analysis, so that the spatial side of the growth and development of space can be known. The analysis method was carried out using Participatory Mapping and Focus Group Discussion (FGD) instruments. The final result of this research is that the character of the historical landscape and the concept of space can be identified which are divided into 3 core zones, buffer zones and utilization zones. Keywords: Avalokitesvara Vihara, Culture, Ornamentation, Spatial